Pachychoroid Spectrum Disorder Findings in Patients with Coronavirus Disease 2019 - Mojtaba Abrishami; Ramin Daneshvar; Nasser Shoeibi; Neda Saeedian; Hamid Reza Heidarzadeh; Seyedeh Maryam Hosseini (Case Reports in Ophthalmological Medicine, 2021)
Purpose. To report the occurrence of acute, bilateral, central serous chorioretinopathy (CSC), and pachychoroid spectrum disorder findings in patients with coronavirus disease 2019 (COVID-19). Methods. In recovered cases of COVID-19 with visual disturbances, complete ocular examinations with multimodal retinal and choroidal evaluation, including enhanced depth imaging optical coherence tomography, fluorescein or indocyanine green angiography, and blue autofluorescence, were obtained. Results. Four COVID-19 recovered patients presented with bilateral blurred vision. Ocular examination and imaging revealed pachychoroid and pachyvessels associated with choroidal hyperpermeability without any obvious intraocular inflammation. Bilateral localized serous retinal detachment was obvious in three cases compatible with pachychoroid associated with CSC manifestation and pachychoroid pigment epitheliopathy in one patient. CSC was resolved with treatment by steroidal antimineralocorticoid (Eplerenone) in two patients and by photodynamic therapy in one patient. None of the patients reported emotional stress and history of corticosteroid consumption. Conclusion. Hyperpermeability of the choroid, pachychoroidopathy, or choroidal vessel congestion can be observed or exacerbated in association with COVID-19.